Does smallness affect the liberalisation of telecommunications? the case of Cyprus - Symeou, Pavlos C. (My University, 2009)
A review of the literature on small economies and on telecommunications policy suggests that policy makers disregard the possible effects of the size of the economy on liberalisation outcomes. This paper builds on the literature on small economies to classify economy size according to economic, demographic, and geographical measures in order to empirically examine whether small size affects the effective culmination of liberalisation of telecommunications. A cluster of small economies that have a maximum population of 9.2 million (Guinea), GDP of US $86.17 billion (Singapore), and arable area of 19.3 thousand km2 (Central African Republic) are the main focus of analysis. In particular, the paper capitalises on an in-depth analysis of the liberalisation of telecommunications in Cyprus and an econometric analysis of the respective European experience. The country-specific outcomes of liberalisation in Cyprus are consistent with the general tendency in small European economies and jointly provide strong evidence that smallness affects the success of liberalisation. The paper concludes with an array of policy suggestions for small economies.
Keywords: Cyprus; European Union; Small economies; Liberalisation; Telecommunications; Competition policy